COMPARISON OF THE MODERN DIAGNOSTIC METHODS FOR GALLSTONES DISEASE IN COMMON BILE DUCT AND GUIDELINES FOR THEIR GRADED USE - Davorin Dajčman; Marjan Skalicky; Zdravko Tošovič (Zdravniški Vestnik, 2004)
Background. The differential diagnosis of biliary diseases remains a challenge. Endoscopic retrograde cholangiopancreatography (ERCP) was the gold standard for pancreaticobiliary evaluation but it is associated with complications. Less invasive diagnostic alternatives with similar capabilities may be cost-effective, particularly in situations involving low prevalence of disease. EUS is a modality for bile duct visualization that could lower costs and prevent ERCPrelated complications. EUS, an accurate and minimally invasive modality, may limit ERCP to therapeutic use in biliary pancreatitis. With recent technological advances, however, the role of ERCP has become more therapy oriented also for other biliary diseases. EUS is recommended if ultrasonography have failed to detect common bile duct (CBD) stones. Recent studies demonstrate that magnetic resonance cholangiopancreatography (MRCP) is comparable to ERCP in the detection of choledocholithyasis. Conclusions. The aim of this article is to compare the performance of endoscopic ultrasound (EUS) and magnetic resonance cholangiopancreatography (MRCP) with ERCP and represent our diagnostic and therapeutic guidelines in the patients with suspected common bile duct stones.